On the Quality of Street Lighting in Pedestrian Crossings - Malgorzata Zalesinska; Krzysztof Wandachowicz (Energies, 2021)
The pedestrian is the least protected road user. A large number of accidents involving pedestrians occur at pedestrian crossings. Bad lighting or a complete lack of it is one of the causes of accidents in these places. Currently, there are no uniform requirements in Europe for the lighting of pedestrian crossings. Each country is trying to create its system of requirements and assessment of lighting of pedestrian crossings. Measurement procedures and required lighting parameter values often vary significantly across countries. This paper discusses the results of measurements carried out at selected pedestrian crossings using two different measurement grids. The lighting quality at the tested crossings has been assessed based on the lighting requirements in force in two EU countries. In addition, we present the results for the illuminance contrast of a measurement board, representing the silhouette of a pedestrian on a crossing, with the background. Based on the determined contrast, we attempted to verify the lighting conditions using an evaluation system described in the literature, which employs fuzzy logic algorithms.